2008
DOI: 10.1039/b716109c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-enhanced polyurethane scaffolds fabricated by thermally induced phase separation

Abstract: Nanocomposite foams are an attractive prospect in a number of fields including biomedical science, catalysis and filtration. In biomedical engineering, porous nanocomposite scaffolds can potentially mimic aspects of the nanoscale architecture of the extra-cellular matrix, as well as enhance the mechanical properties required for successful weight-bearing implants. Thermoplastic polyurethane-multi-walled carbon nanotubes (CNTs) foams were manufactured by thermally induced phase separation (TIPS). TIPS proved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 56 publications
2
73
0
Order By: Relevance
“…62,[113][114][115] Jell et al performed experiments on polyurethane-CNT nanocomposite (a porous structure) and concluded that the amount of MWNT in the scaffold's structure altered the resulting foam's physical, mechanical, and surface properties, and also the osteoblast phenotype. 116 The surface roughness of CNT scaffolds was also found to influence the increase of osteoblastic cell differentiation and proliferation. 86 CNT composites have been shown to have highly textured surfaces; therefore, it is expected for them to influence osteoblast behavior.…”
Section: -105mentioning
confidence: 99%
See 1 more Smart Citation
“…62,[113][114][115] Jell et al performed experiments on polyurethane-CNT nanocomposite (a porous structure) and concluded that the amount of MWNT in the scaffold's structure altered the resulting foam's physical, mechanical, and surface properties, and also the osteoblast phenotype. 116 The surface roughness of CNT scaffolds was also found to influence the increase of osteoblastic cell differentiation and proliferation. 86 CNT composites have been shown to have highly textured surfaces; therefore, it is expected for them to influence osteoblast behavior.…”
Section: -105mentioning
confidence: 99%
“…Furthermore, the rise in roughness might contribute to higher adsorption of fibronectin and vibronectin proteins, increasing the adhesion of cells onto the surface matrices. 113,116,117 When it comes to osteoclast differentiation, it can be inhibited by MWNTs. Osteoclastic activity is related to the natural resorption of bone tissue, but sometimes can lead to pathological conditions such as osteoporosis and rheumatoid arthritis.…”
Section: -105mentioning
confidence: 99%
“…As expected the incorporation of inorganic fillers into the polymer matrix does effect the surface properties, i.e., the wettability and z-potential, of the polymer. [47,48] The incorporation of increasing loading fractions of T5 filler into PLDL results not only improved water wettability of the PLDL but also has a dramatic effect on the measured z-potentials; the iep shifts toward lower pH values and in a steady decrease in the z plateau values. In fact the iep could not be measured anymore for the composites containing the T5 powder.…”
Section: Surface Characteristics Of Titanium Doped Phosphate Glass Plmentioning
confidence: 99%
“…TIPS is thus a very convenient methodology for fabricating porous materials as scaffold architectures that can be obtained by means of the manipulation of processing parameters and system properties. A variety of polymers scaffolds as Polylactic Acid He L et al, 2009); Polyurethane (Guan J et al,2005;Martinez et al, 2006;Fromstein et al 2002), Polycaprolactone[15] and others have been prepared by TIPS technique, also blends of polymers [Martel et al, 2010;Maquet et al, 2001), and composite of polymers with nanohydroxyapatite , Carbon nanotubes Jell et al, 2008) and other have been successfully fabricated. …”
Section: Introductionmentioning
confidence: 99%